TEKNIK PENYUTRADARAAN DENGAN MENGOPTIMALKAN VISUAL DRAMATIK DALAM PRODUKSI PROGRAM DOKUMENTER â€œLENTERAâ€ - Arif Budiman, Dhinda Martina Oktafiani Herlina (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTLentera is the  title of a documentary that tells about the children who living with HIV/AIDS. Where these children live in a foundation special for children with HIV/AIDS called Lentera Foundation. This documentary is not only tells about the live of children with HIV/AIDS, but also gives informations to the audience what is HIV/AIDS, HIV transmission, and how to treat HIV. In this documentary the human interest side will be more highlighted. The dramatical visual and storyline making this documentary an interesting movie.The selection theme  about HIV/AIDS is an anti-mainstream and HIV/AIDS also a big issue  in Indonesia nowadays. This issue certainly  will attract the audience to watch this documentary. With the right illustration music and suitable with the visual will more dramatize the scene. Even though use the illustration music, but the sound of ambience still audible. Director is a person who directs a program that is involved in the creative process from pre to post production, both for drama and non drama. The director is fully responsible for the production process and in charge of leading the production. Keywords: Documentary, Director, Lentera